SOSIALISASI STUNTING “MAKAN TAK HANYA KENYANG TAPI BERGIZI” DI TK NEGERI PEMBINA, DESA BENTENG HILIR - Dian Iriani; Diana Sari; Ratih Hardia Tiningtias (COVIT (Community Service of Health), 2022)
This activity is carried out in the village Benteng Hilir. The title for this outreach activity is “SOSIALISASI STUNTING “MAKAN TAK HANYA KENYANG TAPI BERGIZI”. The purpose of the activities carried out by these students is to increase information and education to all guardians of the TK Negeri Pembina students regarding stunting and child nutrition. The material explained in the form of the characteristics of children suffering from stunting, the factors causing stunting, the impact of stunting, and the supplementary food program (PMT) that can be given to children. This activity is done in kindergarten village Negeri Pembina with student guardian. Keywords: Stunting, Nutrition, PMT